Interferon gamma effect on immune mediator production in human nerve cells infected by two strains of Toxoplasma gondii - Mammari Nour; Vignoles Philippe; Halabi Mohamad Adnan; Dardé Marie-Laure; Courtioux Bertrand (Parasite, 2015)
Interferon gamma (IFN-γ) is the major immune mediator that prevents toxoplasmic encephalitis in murine models. The lack of IFN-γ secretion causes reactivation of latent T. gondii infection that may confer a risk for severe toxoplasmic encephalitis. We analyse the effect of IFN-γ on immune mediator production and parasite multiplication in human nerve cells infected by tachyzoites of two T. gondii strains (RH and PRU). IFN-γ decreased the synthesis of MCP-1, G-CSF, GM-CSF and Serpin E1 in all cell types. It decreased IL-6, migration inhibitory factor (MIF) and GROα synthesis only in endothelial cells, while it increased sICAM and Serpin E1 synthesis only in neurons. The PRU strain burden increased in all nerve cells and in contrast, RH strain replication was controlled in IFN-γ-stimulated microglial and endothelial cells but not in IFN-γ-stimulated neurons. The proliferation of the PRU strain in all stimulated cells could be a specific effect of this strain on the host cell.